Prevalence and antimicrobial susceptibilities of bacteria isolated from blood cultures of hospitalized patients in the United States in 2002 - Thornsberry Clyde; Draghi Deborah C; Jones Mark E; Karlowsky James A; Sahm Daniel F; Volturo Gregory A (BMC, 2004)
Abstract Background Bloodstream infections are associated with significant patient morbidity and mortality. Antimicrobial susceptibility patterns should guide the choice of empiric antimicrobial regimens for patients with bacteremia. Methods From January to December of 2002, 82,569 bacterial blood culture isolates were reported to The Surveillance Network (TSN) Database-USA by 268 laboratories. Susceptibility to relevant antibiotic compounds was analyzed using National Committee for Clinical Laboratory Standards guidelines. Results Coagulase-negative staphylococci (42.0%), Staphylococcus aureus (16.5%), Enterococcus faecalis (8.3%), Escherichia coli (7.2%), Klebsiella pneumoniae (3.6%), and Enterococcus faecium (3.5%) were the most frequently isolated bacteria from blood cultures, collectively accounting for >80% of isolates. In vitro susceptibility to expanded-spectrum β-lactams such as ceftriaxone were high for oxacillin-susceptible coagulase-negative staphylococci (98.7%), oxacillin-susceptible S. aureus (99.8%), E. coli (97.3%), K. pneumoniae (93.3%), and Streptococcus pneumoniae (97.2%). Susceptibilities to fluoroquinolones were variable for K. pneumoniae (90.3-91.4%), E. coli (86.0-86.7%), oxacillin-susceptible S. aureus (84.0-89.4%), oxacillin-susceptible coagulase-negative staphylococci (72.7-82.7%), E. faecalis (52.1%), and E. faecium (11.3%). Combinations of antimicrobials are often prescribed as empiric therapy for bacteremia. Susceptibilities of all blood culture isolates to one or both agents in combinations of ceftriaxone, ceftazdime, cefepime, piperacillin-tazobactam or ciprofloxacin plus gentamicin were consistent (range, 74.8-76.3%) but lower than similar β-lactam or ciprofloxacin combinations with vancomycin (range, 93.5-96.6%). Conclusion Ongoing surveillance for antimicrobial susceptibility remains essential, and will enhance efforts to identify resistance and attempt to limit its spread.